2020
DOI: 10.15407/jnpae2020.04.328
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of status of small rodents’ natural populations from the transformed ecosystems of the Chornobyl exclusion zone according to the complex of biological indicators

Abstract: Morphophysiological and hematological parameters of different species and ontogenesis types of mice rodents from the drained areas of the Chornobyl cooling pond were studied for the first time; comparative analysis, including data of control and stable populations of the Chornobyl exclusion zone, was performed. Radioecological characterization of the research sites was carried out; the contents of the main dose-forming radionuclides were determined; animals’ exposure doses were estimated. In all experimental g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…It was found that most of the leukogram indicators had only a tendency to change (increase/decrease): an increase in the percentage of eosinophils and monocytes against the background of a decrease in lymphocytes. However, it should be noted that in all experimental animals, an increase in the absolute number of leukocytes, granulocytes and monocytes was observed compared to the data of non-irradiated controls (Lypska et al, 2020), while eosinophils had only a tendency to increase in experimental animals from polygons I and II. The presence of a blood-borne parasitic infection did not lead to a significant decrease in erythrocytes in the peripheral blood, but it should be noted that in all blood smears, erythrocyte pathology was recorded: Joly bodies and nuclear erythrocytes, anisocytosis, polychromatophilia, which indicates a violation of the maturation of erythroid cells and may be due to the presence of pathogens of infectious and protozoan diseases in the body.…”
Section: Resultsmentioning
confidence: 60%
“…It was found that most of the leukogram indicators had only a tendency to change (increase/decrease): an increase in the percentage of eosinophils and monocytes against the background of a decrease in lymphocytes. However, it should be noted that in all experimental animals, an increase in the absolute number of leukocytes, granulocytes and monocytes was observed compared to the data of non-irradiated controls (Lypska et al, 2020), while eosinophils had only a tendency to increase in experimental animals from polygons I and II. The presence of a blood-borne parasitic infection did not lead to a significant decrease in erythrocytes in the peripheral blood, but it should be noted that in all blood smears, erythrocyte pathology was recorded: Joly bodies and nuclear erythrocytes, anisocytosis, polychromatophilia, which indicates a violation of the maturation of erythroid cells and may be due to the presence of pathogens of infectious and protozoan diseases in the body.…”
Section: Resultsmentioning
confidence: 60%
“…It was found that most of the leukogram indicators had only a tendency to change (increase/decrease): an increase in the percentage of eosinophils and monocytes against the background of a decrease in lymphocytes. However, it should be noted that in all experimental animals, an increase in the absolute number of leukocytes, granulocytes and monocytes was observed compared to the data of non-irradiated controls (Lypska et al, 2020), while eosinophils had only a tendency to increase in experimental animals from polygons I and II. The presence of a blood-borne parasitic infection did not lead to a significant decrease in erythrocytes in the peripheral blood, but it should be noted that in all blood smears, erythrocyte pathology was recorded: Joly bodies and nuclear erythrocytes, anisocytosis, polychromatophilia, which indicates a violation of the maturation of erythroid cells and may be due to the presence of pathogens of infectious and protozoan diseases in the body.…”
Section: Resultsmentioning
confidence: 60%
“…Зазвичай дослідження дії іонізуючих випромінювань на організм дрібних ссавців, до яких належать і мишоподібні гризуни, проводять на тваринах, які мешкають на забруднених радіонуклідами територіях, де прямо чи опосередковано зазнають постійного впливу опромінення, що відображається як на загальному стані організму, так і на системі кістковомозкового кровотворення, яка є високочутливою до радіаційного чинника. Відповідна наукова робота впродовж багатьох років проводиться співробітниками відділу радіобіології та радіоекології Інституту ядерних досліджень НАН України [1,2].…”
Section: вступunclassified